Assessment of Bone Formation After Secondary Alveolar Bone Grafting With and Without Platelet-Rich Plasma Using Computer-Aided Engineering Techniques. Issue 2 (March 2020) - Chen, Shuxiu; Liu, Bing; Yin, Ningbei; Wang, Yongqian; Li, Haidong
Abstract : Abstract: The aim of this study was to analyze the newly formed bone volume (FV), 6 months after secondary alveoloplasty using iliac cancellous bone graft, with and without platelet-rich plasma (PRP). Forty patients with unilateral alveolar cleft were involved in this randomized, prospective, comparative study, with 20 patients each forming the control (group A) and PRP (group B) groups, respectively. The preoperative alveolar defect volume (DV) and the postoperative FV were automatically calculated by the computer-aided engineering software using the patients' pre and postsurgical computed tomography data. The volume of the actual bone graft (AV) was identical to the DV calculated before surgery. The bone formation ratio (BF%) was calculated as follows: BF% = (FV/AV) × 100%. The mean BF% was 42.54 ± 9.32% in group A and 46.97 ± 18.49% in group B. There was no statistically significant difference between the 2 groups for BF% ( P > 0.05). The study presents a fast and accurate method for assessing the effect of PRP in alveolar grafting. However, the study found no conclusive evidence on the effect of PRP on bone growth. Abstract : Supplemental Digital Content is available in the text